Gendered Land Ownership and Rural Household Welfare: Evidence from Indonesia - Nila Cahayati; Fajar Try Leksono; Thomas Soseco; Isnawati Hidayah (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2026)
This paper studies how land ownership is gendered within rural Indonesian households and whether women’s land ownership is associated with household welfare, female labor participation, and food security. Using nationally representative SUSENAS 2018 household and individual modules, construct land ownership typologies that distinguish ownership by the male household head, the spouse, children, other members, and multiple‑owner arrangements. Weighted OLS models with province fixed effects and district‑clustered standard errors show that households where the spouse owns land exhibit higher per‑capita expenditure than otherwise similar landowning households. Logistic models indicate that female land ownership is positively associated with women’s labor participation but is not significantly linked to food insecurity, while male ownership is correlated with lower food insecurity. Interaction and split‑sample tests reveal no statistically meaningful heterogeneity between Java and non‑Java regions. The findings support the view that women’s property rights are linked to economic resilience and agency in rural Indonesia, even though some welfare measures based on non‑monetary living conditions respond differently. Policies that expand women’s land titles, secure joint ownership, and complement land programs with human‑capital and market access interventions are likely to yield broad welfare gains.